The Extent of Undergraduate Student Participation in Conducting Scientific Research at the University of Nizwa in the Sultanate of Oman: - Al-Habsi, Radhiya Sulaiman; Al-Maadi, Ikram Hamad Ali; Al-Salmani, Ammar Saeed Amer (Journal of Educational and Psychological Sciences, 2023)
The study aimed at investigate the extent of undergraduate students' participation in scientific research at the University of Nizwa in the Sultanate of Oman. Additionally, the study aimed to identify whether there were statistically significant differences, at the significance level (α≤0.05), in the means of the study variables, namely gender and specialization. To achieve these objectives, an analytical descriptive approach was employed, and a questionnaire was developed to gather data from a sample of 380 undergraduate students, representing both male and female students across all disciplines out of a total of 5821 students. The study results showed that: The findings of this study indicate a high level of participation by undergraduate students in conducting scientific research at the University of Nizwa in the Sultanate of Oman. However, the results also revealed statistically significant differences (α≤0.05) in the responses of the study sample members due to the gender variable, with male students exhibiting higher levels of participation, and the specialization variable, with literary majors showing greater levels of participation.The study proposes a number of interventions to increase the level of involvement of faculty members in scientific research conducted by undergraduate students at the University of Nizwa. These interventions involve the establishment of an annual competition for scientific research conducted in partnership with undergraduate students, as well as the provision of annual financial incentives for faculty members who publish at least one research paper in peer-reviewed scientific journals in conjunction with undergraduate students during the academic year. Such measures are expected to promote faculty engagement and incentivize collaborative research efforts between faculty members and undergraduate students at the University of Nizwa.
Keywords: faculty members; undergraduate students; scientific research; University of Nizwa; Sultanate of Oman